2021
DOI: 10.1111/ijac.13964
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of n‐HAP using different precursors and dependence of Vickers hardness on the structure by tuning sintering temperature

Abstract: Three sets of starting materials Ca(NO3)2·4H2O and (NH4)2HPO4; Ca(OH)2 and H3PO4; Ca(OH)2 and (NH4)2HPO4 were chosen for the preparation of different precursors of hydroxyapatite nanoparticles (n‐HAP) by wet chemical precipitation technique denoted by HAP‐1, HAP‐2, HAP‐3. X‐ray diffraction (XRD) studies show that n‐HAP of all three types exhibited single‐phase in the as‐prepared condition. Transmission electron microscopy (TEM), high‐resolution transmission electron microscopy (HRTEM), and selected area electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…However, the sintering process also significantly enhanced the hardness of xenogeneic bone grafts. Similar changes are also found in the production of synthetic HAp [49]. In comparison, our granules were produced in a biomimetic precipitation process and did not involve a sintering process.…”
Section: Hardness Of Bpnccap and Bio-oss ®supporting
confidence: 70%
“…However, the sintering process also significantly enhanced the hardness of xenogeneic bone grafts. Similar changes are also found in the production of synthetic HAp [49]. In comparison, our granules were produced in a biomimetic precipitation process and did not involve a sintering process.…”
Section: Hardness Of Bpnccap and Bio-oss ®supporting
confidence: 70%
“…Then, the heating rate is increased to 2 °C/min up to 1200 °C with a soaking time of 1 h to complete the heat treatment process. This process ensures that the scaffolds are fully formed and hardened, creating a strong and durable structure [ 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…The results demonstrated that the phosphate compound that gave more amount of phosphate ions would prepare HAP more efficiently [28]. Ishtiaque et al prepared nano-HAP by wet chemical precipitation and concluded that starting materials would influence the thermal stability and hardness of HAP [29]. To this end, commercially available chemical reagents would be used as an alternative by dissolving in a water solution to generate a uniform precipitate and a high-purity nano-powder material would be obtained after post-reaction processing.…”
Section: Figure 1 Key Factors For Biomimetic Preparation Of Nano-hap ...mentioning
confidence: 99%